Physical activity and sedentary behavior in women with rheumatoid arthritis: a comparison of patients with low and high disease activity and healthy controls - Summers G (Dove Medical Press, 2019)
Gregory Summers,1 Alison Booth,1 Katherine Brooke-Wavell,2 Tharaq Barami,1,3 Stacy Clemes21Department of Rheumatology, Royal Derby Hospital, Derby, UK; 2School of Sport, Exercise and Health Sciences, Loughborough University, Loughborough, UK; 3Kettering General Hospital, Kettering, UKObjective: In rheumatoid arthritis (RA) patients, low levels of physical activity (PA) and high levels of sedentary behavior (SB) may play a role in enhancing cardiovascular risk. We do not know how long-term control of disease activity impacts upon daily PA levels and if treated patients attain PA levels seen in healthy controls. We therefore compared habitual levels of PA and SB between female RA patients with low disease activity achieved by anti-tumor necrosis factor (TNF) therapy, those with active arthritis (aRA) and non-RA controls.Methods: We carried out a cross-sectional comparison of 40 RA patients on anti-TNF therapy for >2 years with DAS28<3.2 (tRA), 32 patients on conventional disease modifying anti-rheumatic drugs with DAS28>3.2 (aRA) and 34 healthy controls (C) with the groups matched for age and body mass index. PA was assessed using the ActiGraph accelerometer to determine step count and time spent in moderate-to-vigorous physical activity (MVPA), light activity and sedentary time.Results: Daily step count was 72% higher in tRA and 40% higher in C in comparison to aRA (p<0.01). Sedentary time (as a proportion of wear time) was 10% less in tRA than aRA (p=0.03), while light activity time was 18% higher (p=0.014). Both RA groups had 40% lower MVPA time than C (p=0.001). Only half of either RA group fulfilled current WHO guidelines for PA compared with 82% of controls.Conclusion: RA patients who had long-term disease suppression were more physically active with less SB compared to RA patients with active disease. They had similar light PA and SB to controls although lower MVPA. Behavioral change interventions are likely to be needed in order to restore moderate exercise, further reduce SB and to meet guidelines for daily PA.Keywords: rheumatoid arthritis, physical activity, sedentary behavior, accelerometry